Hepatitis A virus infection presenting with seizures - ERTEM ŞAHİNOĞLU, DENİZ (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Hepatitis A infection rarely causes extrahepatic manifestations. Here we present a 5-year-old patient with an initial complaint of nuchal rigidity and convulsions during the course of hepatitis A infection. Because hepatitis A virus RNA was demonstrated in the cerebrospinal fluid, it was thought that convulsions might be related to this viral infection.
Keywords: hepatitis A; convulsion; extrahepatic; child; neurologic complication; EPIDEMIC